Effectiveness in Implementing the School Mover Program in North Kalimantan Province - Suprapto, Joko; Hasniati , Hasniati; Ibrahim, Muh. Akmal; Syahribulan, Syahribulan (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study discusses the effectiveness of the school driving program in North Kalimantan province based on the Decree of the Minister of Education, Culture, Research, and Technology Number 371/M/2021 concerning the School Driving Program. This program includes interventions in five domains, namely consultative and asymmetric assistance, strengthening school human resources, learning with a new paradigm, data-based planning, and school digitalization. In North Kalimantan itself, this program has been implemented from 2021 to 2024 before its implementation ended in early 2025. This study uses a qualitative research method by observing the implementation of this program in North Kalimantan province. The results of this study indicate that the implementation of the school driving program in North Kalimantan province has not been effective. This is due to the difficulty of access to several schools and the slow adjustment of teaching staff to the independent curriculum implemented by the government.